The effect of Helicobacter pylori eradication on symptoms and gastric emptying in patients with nonulcer dyspepsia - Cansel TÜRKAY; İrfan SOYKAN and Metin KIR and Ali ÖZDEN (Turkish Journal of Gastroenterology, 2019)
-